The Relationship Among Maternal Parenting Stress, Coping, and Depressive Symptoms Across Time - (:unkn) unknown (My University, 2012)
This study was a secondary analysis in which the relationship among maternal parenting stress, coping, and depressive symptoms over time in 161 low-income mothers who participated in an Early Head Start Pathways Project were examined. Measurements were assessed longitudinally over a 12 year period of time. Direct and indirect relationships were proposed between maternal mastery, pre-existing depressive symptoms, relationship with significant other, child behavior, child temperament, maternal parenting stress, coping, and later depressive symptoms. Results from path analyses showed that when assessed earlier in the childbearing years, mastery, depressive symptoms, relationship with significant other, child temperament, child behavior, and maternal parenting stress are associated with later depressive symptoms in the mother at 36 months, Pre-Kindergarten and at Grade Five. There were no direct effects of maternal parenting stress on later depressive symptoms, and coping did not serve as mediator between maternal parenting stress and later depressive symptoms.
Keywords: Coping; Depression; Depressive Symptoms; Maternal Stress; Mothers; Parenting Stress